Ecological properties of soil improved by high-performance ester materials under freeze-thaw cycles conditions. - Cuiying Zhou; Qingxiu Zhang; Jin Liao; Haoqiang Lai; Zhen Liu (PLoS ONE)
High-performance ester materials (HPEMs) are widely applied in slope soil restoration owing to their biodegradability, with a predictable degradation cycle of 2-3 years. Although HPEMs have been extensively studied for tropical applications, their performance in cold regions subject to frequent freeze-thaw cycles (FTCs) remains poorly understood. We hypothesize that FTCs degrade HPEM performance but enhance plant germination. Controlled experiments demonstrated that FTCs reduced material viscosity by 70.5% and water absorption by 52%, while increasing germination rates by 30%, revealing a trade-off between material durability and ecological benefits. Additionally, the field water holding capacity and soil conductivity of the improved soil decrease. Based on these experimental results, the study establishes quantitative relationships between FTCs and soil ecological properties improved by HPEMs. Quantitative relationships revealed linear viscosity decline and exponential water absorption decay trends, with high correlation coefficients (R² ≥ 0.95). This study establishes a comprehensive theoretical framework for predicting the service life of ester materials in cold regions and optimizing their application strategies.